Copyright problem in the age of communication (review of publications) (Herald of Journalism, 2016)
Intellectual property protection can impact negatively on economic and cultural development of the country. The main aim of today’s copyright system is to give certain companies the power over society, which they use for enriching themselves. Today, copyright protects the rights of authors; in particular, in the field of literature and arts, that is, it reaches the purpose for which it was created, but it does so high costs for which consumers pay with their freedom and their money. Convincing arguments against intellectual property rights are set out in a recent book Against Intellectual Monopoly written by Michel Boldrin and David Levine, two American economists, as well as the book Against Intellectual Property by Stephan Kinsella, the American lawyer. In the view of many other experts, total intellectual propertyprotection begins to hinder seriously developing science and culture.
Keywords: copyright system; copyright; intellektual properpy